Social support and parent-child relationship among adolescents and their influence on emotions - ZHOU Changyuan; DAI Luojia; HE Yaping; ZHU Jingfen (Shanghai yufang yixue, 2023)
ObjectiveTo explore the association between social support， parent-child relationships， and depression， anxiety， and loneliness among adolescents， in order to provide a reference for improving mental health in youth.MethodsA total of 11，596 middle school students from two districts of Shanghai were investigated with the stratified random cluster sampling method. The Chinese version of Patient Health Questionnaire （PHQ-2-C）， Generalized Anxiety Disorder （GAD-7）， UCLA Loneliness Scale （ULS-6）， Perceived Social Support Scale and Parent-child Cohesion Questionnaire were used in the survey. Statistical inferences were made using t-test， ANOVA， and logistic regression analysis.ResultsGirls， non-graduates， students ranking in the top 25%， adolescents living with parents and with higher socioeconomic status had higher scores of social support and parent-child cohesion than boys， graduates， students ranking in the middle or in the bottom 25%， adolescents not living with parents and with lower socioeconomic status （P<0.05）. Adolescents' parent-child cohesion and social support were negatively correlated with all kinds of emotions. Parent-child cohesion was an associated factor of depression （OR=0.93， 95%CI：0.91‒0.94）， loneliness （OR=0.94， 95%CI：0.94‒0.95） and anxiety （ORmild=0.98， 95%CI： 0.98‒0.99； ORmoderate or severe=0.96， 95%CI： 0.95‒0.98）， but there were differences in the correlation between emotions and social support in different dimensions.ConclusionSocial support and parent-child relationship are significantly associated with depression， anxiety and loneliness in adolescent students. Paying more attention to youth with different characteristics， taking targeted measures to improve the level of social support and establishing a good family relationship are conducive to promoting the mental health of adolescents.